ARIMA (p, d, q) Modeling for Predicting Exports of Fresh and Chilled Fish Based on Market Conditions and Main Destination Countries : The Case of Indonesia 2012-2022 - Handayani, Vitri Aprilla; Sulistyono, Eko; Sunarsono, Hery; Arafi, Adamsyam; Harahap, Diana Sari (Statistika, 2024)
ABSTRACT Fresh and chilled fish are the largest contributor to Indonesia's fishery product exports, accounting for a share of 45% or around USD 2.2 billion in 2021. The main destination countries for Indonesia's fresh and chilled fish exports include China, the United States, Japan, and other European countries. This research aims to analyze the factors influencing the export value of Indonesia's fresh and chilled fish, as well as to identify and evaluate the ARIMA (p, d, q) model based on historical data from 2012-2022. The result is an ARIMA (4,2,2) model with a MAPE value of 2.208 and a predicted value for the 2023 period of 4351 tons. This is in line with the large exports of fresh fish from Indonesia to various destination countries.